2021
DOI: 10.3389/fcell.2021.678117
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Optimal Autologous Cellular Platforms for Prenatal or Perinatal Factor VIII Delivery to Treat Hemophilia A

Abstract: Patients with the severe form of hemophilia A (HA) present with a severe phenotype, and can suffer from life-threatening, spontaneous hemorrhaging. While prophylactic FVIII infusions have revolutionized the clinical management of HA, this treatment is short-lived, expensive, and it is not available to many A patients worldwide. In the present study, we evaluated a panel of readily available cell types for their suitability as cellular vehicles to deliver long-lasting FVIII replacement following transduction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 103 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…With regard to tissue-resident EPCs, pre-cultured human CD31 + c-Kit + VEGFR + cells isolated form umbilical cord tissue (UCT) EPCs have been shown to express similar levels of F8 gene mRNA as cultured hLSECs. Moreover, retroviral-FVIII-transduced UCT-EPCs have proved to be highly amenable to expressing vector-encoded FVIII, producing levels of mRNA, protein, and procoagulant activity that far exceeded those of transduced LSECs, which are thought to be the body’s primary site of FVIII synthesis [ 203 ].…”
Section: Clotting Factor Biosynthesismentioning
confidence: 99%
“…With regard to tissue-resident EPCs, pre-cultured human CD31 + c-Kit + VEGFR + cells isolated form umbilical cord tissue (UCT) EPCs have been shown to express similar levels of F8 gene mRNA as cultured hLSECs. Moreover, retroviral-FVIII-transduced UCT-EPCs have proved to be highly amenable to expressing vector-encoded FVIII, producing levels of mRNA, protein, and procoagulant activity that far exceeded those of transduced LSECs, which are thought to be the body’s primary site of FVIII synthesis [ 203 ].…”
Section: Clotting Factor Biosynthesismentioning
confidence: 99%
“…This is especially true for the hLSECs, which exhibit very slow division kinetics and cannot be propagated for more than a couple of passages in vitro prior to senescing. The PLCs employed in the present study exhibit a phenotype and biological properties that closely resemble that of MSC from other tissues ( 3 , 22 , 68 ). It is noteworthy that prior studies have reported the downregulation of components of the DNA damage response (DDR) and HRR pathways in MSC with time in culture ( 94 96 ).…”
Section: Discussionmentioning
confidence: 87%
“…While current clinical trials are employing direct injection of AAV-based vectors (7)(8)(9)(10)(11)(12)(13), the use of gene-modified cells as vehicles to accomplish gene "addition" has many advantages from a manufacturing standpoint, as it allows multiple safeguards to be added to the production process (57). In an effort to make cell-based gene therapy a clinical reality for HA, we and others have performed studies over the past decades to identify the ideal cell type for delivering a fVIII transgene and the optimal vector to introduce the fVIII transgene into the desired cell population (3,22,31,34,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Previously, we demonstrated the advantages of using lentivector-transduced PLCs as the cellular vehicle for delivering a fVIII transgene (22,68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 93 94 95 Moreover, retroviral FVIII-transduced human umbilical cord-derived ECFCs are superior to transduced LSECs (liver sinusoidal endothelial cells) in terms of mRNA production, protein levels, and procoagulant activity. 96…”
Section: Ecfcs For Potential Therapeutic Applicationsmentioning
confidence: 99%